Language choice in a multilingual refugee community: Evidence from the Viqueque people in Oebelo Village - Abdul Rahim Arman Putera Dapubeang; Kristofel Bere Nahak (Universitas Muhammadiyah Malang, 2026)
Migration and forced displacement often create complex multilingual environments in which communities must negotiate between maintaining their heritage language and adapting to dominant languages in the host society. In such contexts, language choice becomes a key sociolinguistic phenomenon reflecting social interaction, identity formation, and language maintenance. However, studies on language choice and language shift within refugee communities in Indonesia remain limited. This study investigates language choice among the Viqueque community in Oebelo Village, Kupang Regency, a refugee group originating from East Timor following the 1999 referendum. This research employed a mixed-method approach combining quantitative and qualitative techniques. Data were collected through questionnaires and semi-structured interviews with 287 respondents, consisting of 181 adults and 106 adolescents. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed thematically to explore sociolinguistic factors influencing language choice. The findings show that Tetun, Indonesian, and the Kupang Malay dialect are actively used in the family domain, with significant generational differences. Among adults, Tetun remains dominant in spousal communication (63–66.3%), whereas Indonesian is more frequently used in parent–child interactions (60.1–65.2%). In contrast, adolescents predominantly use Indonesian with parents (61.3–70.8%), while the Kupang Malay dialect dominates sibling interactions (40.5–51.9%). These patterns indicate an intergenerational language shift from Tetun toward Indonesian and Kupang Malay. This study contributes empirical evidence on language choice and heritage language shift in refugee communities, highlighting the crucial role of family interactions in sustaining minority languages within multilingual migrant societies.